Pembangunan Package R untuk Small Area Estimation Pendekatan Nonparametrik Berbasis Kernel Nadaraya-Watson - Wicak Surya Hasani; Azka Ubaidillah (Politeknik Statistika STIS, 2022)
The limited sample in survey activities is an obstacle to providing data in smaller domains and areas. Small Area Estimation (SAE) can be solve this problem. However, this indirect estimation technique requires the assumption of a linear relationship between the mean of a small area and the accompanying variables. This problem can be solved by using a nonparametric approach, one of the nonparametric approaches that can be used is the Nadaraya-Watson Kernel base. To facilitate the implementation, the researcher built a Package R for Small Area Estimation of a nonparametric approach based on the Nadaraya-Watson Kernel with the package name